Diprotin A TFA Exerts Neurovascular Protection in Ischemic Cerebral Stroke - Zhou, Ming-Yue; Zhang, Ya-Jie; Ding, Hong-Mei; Wu, Wei-Feng; Cai, Wei-Wei; Wang, Yan-Qiang; Geng, De-Qin (Frontiers in Neuroscience, 2022)
Background It has been established that the dipeptidyl peptidase-4 (DPP-4) inhibitor Diprotin A TFA can reduce vascular endothelial (VE)-cadherin disruption by inhibiting the increase in cleaved β-catenin in response to hypoxia, thereby protecting the vascular barrier of human umbilical vein endothelial cells. In this study, we sought to investigate the possible effect of Diprotin A TFA on the VE barrier after cerebral ischemic stroke in mice. Methods C57BL/6J mice were divided into five groups, namely, (1) sham, (2) stroke, (3) stroke + dimethyl sulfoxide (DMSO), (4) stroke + Diprotin A TFA, and (5) stroke + Diprotin A TFA + XAV-939. First, the cerebral ischemia model was established by photothrombotic ischemia, followed by intraperitoneal injection with Diprotin A TFA and XAV-939 at doses of 70 μg/kg and 40 mg/kg 30 min once in the morning and once in the evening for 3 days. Immunofluorescence staining and Western blot methods were used to analyze the expression of vascular and blood-brain barrier (BBB)-associated molecular markers in the peri-infarct area. Results Compared with the vehicle control group, we found that mice injected with Diprotin A TFA exhibited reduced cerebral infarction volume, increased vascular area and length around the brain injury, increased pericyte and basement membrane coverage, upregulated expression of BBB tight junction proteins, and improved their BBB permeability, whereas the group injected with both drug and inhibitor exhibited significantly aggravated vascular injury and BBB permeability. Conclusion Diprotin A TFA can reduce VE-cadherin disruption by inhibiting ischemia-hypoxia-induced β-catenin cleavage to protect blood vessels.